Pengaruh Promosi Penjualan dan Influencer Terhadap Keputusan Pembelian Produk Mirelle Beauty Melalui Shopee - Nella Anisa Devi; Urip Mulyadi (INDO PUBLISHING, 2025)
This research is motivated by the increasingly intense competition in Indonesia’s local skincare industry, where local brands strive to create innovative products along with effective marketing strategies to attract consumers. Mirelle Beauty, as one of the local skincare brands, utilizes the e-commerce platform Shopee with sales promotion strategies and influencer support to increase consumer purchase decisions. The purpose of this study is to determine the positive influence of sales promotion and influencers, both partially and simultaneously, on the purchasing decisions of Mirelle Beauty products through Shopee.This study employed a descriptive quantitative approach with a positivist paradigm. The research population consisted of 34,000 followers of the Shopee Mirelle Beauty account, with a sample of 100 respondents determined using the Slovin formula. Data were collected using questionnaires with a Likert scale and analyzed through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS version 26.The results show that sales promotion has a positive and significant effect on purchasing decisions with a significance value of 0.015 (<0.05) and a t-value of 2.466 > t-table 1.984. The influencer variable also has a positive and significant effect on purchasing decisions with a significance value of 0.000 (<0.05) and a t-value of 5.666 > t-table 1.984. Simultaneously, sales promotion and influencers significantly affect purchasing decisions with an F-value of 111.954 > F-table 3.09. The coefficient of determination (R²) is 0.698 or 69.8%, indicating that the two independent variables contribute 69.8% to purchasing decisions, while the remaining 30.2% is influenced by other factors outside this study.The limitation of this research is that it only focuses on the Shopee platform as an e-commerce medium and uses a relatively limited sample size, which may not fully represent all Mirelle Beauty consumers.